1990
DOI: 10.1002/ar.1092270413
|View full text |Cite
|
Sign up to set email alerts
|

Development of the giraffe horn and its blood supply

Abstract: The giraffe horn is an unusual cranial exostosis that lacks clear delineation and categorization as either horn or antler. The distinction between the two is made by contrasting their methods of development and basic composition. This process of development has not been detailed in the giraffe, a factor contributing to the difficulty in distinguishing the classification of these horns. In a chronological series of giraffe horns from prenatal and postnatal animals, we have observed unique morphologies that defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 10 publications
4
30
0
Order By: Relevance
“…[24,29]) as well as to headgear per se (e.g. [11]), we restrict its use to bovid horns (headgear covered in a keratinous sheath that is not annually replaced).…”
Section: Histogenesis Of Ruminant Headgearmentioning
confidence: 99%
See 2 more Smart Citations
“…[24,29]) as well as to headgear per se (e.g. [11]), we restrict its use to bovid horns (headgear covered in a keratinous sheath that is not annually replaced).…”
Section: Histogenesis Of Ruminant Headgearmentioning
confidence: 99%
“…The ossicone begins as a separate bony core above the frontoparietal suture in giraffes and above the frontals in okapis [22]. The ossicone was originally thought to condense as fibrocartilage within the skin above the bone [26,27]; however, Ganey et al [24] showed that it is primarily non-cartilaginous. Although initial ossification occurs dermally, the process is intramembranous, as is typical for skull roof bones [24].…”
Section: Histogenesis Of Ruminant Headgearmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if brain size scales negatively with skull size, sinuses may expand to fill the frontal bone to increase the surface area for attachment of masticatory muscles in large animals. Other hypotheses include decreasing the weight of the skull (Davis et al, 1996;Mitchell and Skinner, 2003;Shea, 1936), providing thermoregulation of the brain (Bremer, 1940;Dyce et al, 2002;Ganey et al, 1990;Skinner, 2003, 2004), shock absorption during head-butting or neck-sparring (Badlangana et al, 2011;Davis et al, 1996;Schaffer and Reed, 1972), serving as a resonance chamber for the production of low frequency sounds (Leakey and Walker, 1997;von Muggenthaler et al, 1999) and dissipation of stress over the skull during mastication, and particularly bone-cracking in carnivores (Buckland-Wright, 1971, 1978Joeckel, 1998;Tanner et al, 2008). Nonetheless, hypotheses regarding sinus function are difficult to test without first obtaining data on sinus variation within and between species.…”
Section: Introductionmentioning
confidence: 99%
“…The modern giraffe possesses exceptionally elongated cervical vertebrae and metapodials; the extinct taxa exhibit varying degrees of neck and limb elongation [4–6]. Giraffidae possess specialized cranial appendages termed ossicones, which start as separate ossifications that subsequently fuse to the skull [2, 79]. Among the Giraffidae, several taxa exhibit atypical ossicone structure, including the sivatheres Sivatherium and Bramatherium and the samothere Schansitherium .…”
Section: Introductionmentioning
confidence: 99%